Indonesia’s Criminal Justice System with Pancasila Perspective as an Open Justice System - Robiatul Adawiyah; Umi Rozah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
The criminal justice system should be an embodiment of values of Pancasila. Few cases raised concerns and questioned Pancasila’s practice because it hurt community justice sense. Pancasila must be reflected in criminal law enforcement. The criminal justice system is open whose operation is influenced by the environment the subsystems's operation, it is very important to be studied comprehensively. This article discusses the Indonesian criminal justice system with a Pancasila perspective; Indonesian criminal justice system with the concept of Pancasila as an open criminal justice system; subsystem in the Indonesian criminal justice system has the concept of Pancasila as an open criminal justice system. The research method in this article is normative with philosophy approach. The results showed that criminal justice system has Pancasila perspective, means that it must prioritize humanity, the balance of the interests of perpetrators and victims, the justice of God, humanity and society (substantive justice). As an open system, it does not work in solitaire in a vacuum, but must pay attention to legal values and community justice sense so that the working of it is more contextual in applying criminal law to achieve its success. And all subsystems in the criminal justice system have basically been based on Pancasila as an open justice system.